Effects Of Pandemic Covid-19 On The Malaysian Economy, Focused On Five Important Industries And Shariah Viewpoints - Muhammad Haiqal bin Tajuden; Muhammad Nabil bin Norhasmy; Muhammad Rizwan Nasution bin Mohd Idris; Muhammad Adham bin Mohamad Ares; Muhammad Faizzuwan bin Mustafa; Fuadah Johari (Halal Tourism Department, Faculty of Islamic Economics and Business, Universitas Islam Negeri Mataram, 2024)
Vol. 13 No. 2